Implementasi Peer Tutoring dalam Pembentukan Karakter pada Pembelajaran Tahsin Al-Qur’an Metode Tilawati - Yulikha Shobarohmi Ishar; Endi Rochaendi; Ahmad Salim (Indonesian Journal of Elementary Education and Teaching Innovation, 2026)
This study investigates the integration of the Tilawati method and the peer tutoring strategy in Qur’anic recitation (tahsin) learning within Islamic elementary education, aiming to describe their implementation, examine their synergy in forming Qur’anic character, and identify the values internalized throughout the learning process. Methodologically, the study employs a qualitative approach with a case study design at SD Islam Al Azhar 31 Yogyakarta. Data were collected through participatory observation of tahsin sessions, in-depth interviews with teachers, peer tutors, and tutees, as well as document analysis (lesson plans, assessment rubrics, and reflective journals). Data analysis followed thematic procedures of reduction, display, and conclusion drawing, with credibility ensured through triangulation of sources and methods, along with member checking. The findings reveal that the combination of Tilawati’s technical structureâ€”accuracy of makhraj, application of tajwÄ«d, and rhythmic tartÄ«lâ€”and the relational dynamics of peer tutoring based on the â€œappreciationâ€“diagnosisâ€“demonstrationâ€“practiceâ€“confirmationâ€ sequence enhances Qur’anic reading competence while reinforcing religiosity, responsibility, discipline, cooperation, and empathy. The transformation from a teacher-centered model to a psychologically safe, collaborative ecosystem was sustained by ritualized practices (talqÄ«nâ€“tasmiâ€˜, tikrÄr, murÄjaâ€˜ah), social co-regulation among students, and post-session spiritual reflection. The study concludes that the Tilawatiâ€“peer tutoring integration effectively bridges the gap between learning to know and learning to be, recommending strengthened peer tutor capacity, technical standard calibration, authentic cognitiveâ€“affective assessment, and parental engagement as home coaches to ensure the sustainability of character habituation. Keywords: Tilawati; peer tutoring; Qur’anic recitation; character formation; Islamic elementary education.